Task-related neural activation abnormalities in patients with remitted major depressive disorder: A coordinate-based meta-analysis. (December 2022) - Wang, Zuxing; Zou, Zhili; Xiao, Jun; Wang, Peijia; Luo, Yuanyuan; Min, Wenjiao; He, Ying; Yuan, Cui; Su, Yihan; Yang, Chenghui; Chang, Fan; Zhu, Hongru
Abstract: Major depressive disorder (MDD) patients demonstrate abnormal neural activation even after complete remission. Many task-related functional magnetic resonance imaging (fMRI) studies have focused on changes in brain function in individuals with remitted MDD (rMDD). We conducted a meta-analysis of these studies to explore differences in brain activation between patients with rMDD and healthy controls (HCs). Our meta-analysis included 13 studies, encompassing 18 experiments, 304 rMDD patients and 321 HCs. Patients with rMDD showed increased neural activation in the left inferior parietal gyrus and right fusiform gyrus and decreased neural activation in the left superior frontal gyrus, right middle temporal gyrus and right Heschl gyrus. Meta-regression analysis revealed that patient age and the number of depressive episodes were negatively associated with brain activity in the left superior frontal gyrus. Our findings suggest abnormal brain function, especially in areas involved in cognitive function, emotion regulation and perception, in rMDD patients; alterations of these regions may be the primary or secondary neurophysiological mechanisms underlying MDD and provide potential neuroimaging targets for early screening. Highlights: A first meta-analysis related to functional magnetic resonance imaging of remitted major depressive disorder was conducted. Neural activation abnormalities in patients with remitted major depressive disorder was found. Remitted major depressive disorder individuals' neural activation involving cognitive function, emotion regulation and perception were abnormal. Mean age was negatively associated with brain activity in the left superior frontal gyrus.